Pilot scale manufacturing of black seed oil-loaded alginate beads; process development, and stability of thymoquinone - Alkhatib, Hamzeh; Mohamed, Farahidah; Alfatama, Mulham; Assadpour, Elham; Kharazmi, Mohammad Saeed; Jafari, Seid Mahdi; Sarker, Md Zaidul Islam; Sadasivuni, Kishor Kumar; Mohmad Sabere, Awis Sukarni; Doolaanea, Abd AlMonem (Elsevier, 2024)
The approach of ionic gelation was employed at the pilot scale of the 50 kg batch size to manufacture black seed oil (BSO)-loaded alginate (ALG) beads as a natural source supplementing the main bioactive compound of BSO, i.e., thymoquinone (TQ). The BSO-ALG emulsion was prepared by initially emulsifying BSO with alginate solution at the pilot scale in two stages. The final emulsion was then dripped through 12 units of 3D-printed multi-nozzles into a curing bath containing Ca2+. The dripping flow rate was scaled up to 288 mL/min through the 3D-printed multi-nozzles (22-gauge). The characteristics of pilot scale BSO-ALG beads were similar to those produced at the lab scale; the beads were spherical with a size of 1.84–1.94 mm. The mechanical strength and loss on drying ranged from 143.6 to 172 g and 77.85–81.96 %, respectively. The production yield and encapsulation efficiency were 77.53–83.65 % and 95.36–97.9 %, respectively. Furthermore, the emulsification process did not affect TQ stability, while the curing process reduced TQ concentration from 1.51 % to 1.03 % w/w. Additionally, a substantial drop in TQ concentration in the encapsulated BSO was observed after the drying process, where it reached 0.23 % w/w. Finally, the stability of BSO-ALG beads in both wet and dried forms under real-time and accelerated conditions for 3 months revealed that beads were stable in terms of their organoleptic characteristics, size and sphericity, and loss on drying. Findings from this study enable the large-scale manufacturing of encapsulated BSO and similar bioactive compounds in ALG beads for the first time. These findings are valuable for advancing microencapsulation through ionic gelation and enhancing food preservation and safety.